Efeitos inibitórios in vitro da atividade da α-amilase pancreática e salivar e ações hipoglicêmicas de taninos condensados e hidrolisáveis - Kato, Camila Gabriel (2016)
In the human organism, five isoenzymes of amylase have been described, three salivary amylases and two pancreatic amylases. Due to the importance in several metabolic disorders including diabetes and obesity, the pancreatic-amylase has been more extensively studied than the salivary α-amylase. In consequence, a series of pancreatic α-amylase inhibitors are available in the market, such as acarbose. However, the human salivary amylase (HSA), has important roles in the mouth, including hydrolysis of dietary starch, binding to the tooth surface, and binding to oral streptococci. All three actions contribute to the process of dental plaque and caries formation. Tannins are one of the most extensively studied molecules able to inhibit amylases. It is generally believed that the discovery of new materials rich in tannins with enzyme inhibitory properties can contribute for the discovery of new drugs useful in the control and treatment of diabetes, obesity and other physiological disorders, such as oral diseases, including caries. One of the most extensively studied condensed tannin (proanthocyanidin) is that extracted from the bark of the black wattle tree (Acacia mearnsii De Wild.). It is rich in the catechin-like flavan-3-ols monomers robinetinidol and fisetinidol. One of the most simple and common hydrolysable tannin is the gallotannin with up to 12 esterified galloyl groups and a core glucose. This structure is particularly abundant in the gallotannin from chinese natural gallnuts. The aim of the article 1 was to compare the in vitro inhibitory effects on the pancreatic α-amylase and the in vivo hypoglycemic actions of a condensed tannin from A. mearnsii bark and a hydrolysable tannin from Chinese natural gall (Rhus chinensis Mill.). For comparative purposes, similar experiments were also run with acarbose, a highly effective inhibitor of pancreatic α-amylase inhibitor. The aim of the article 2 was to investigate the in vitro inhibitory effects on the human salivary α-amylase of the same two tannins in the search of new molecules with an increased affinity and specificity for the enzyme. In both articles, in the in vitro experiments, especial attention has been devoted to the kinetics of the inhibition, with a detailed search for the model that best describes the mechanism of action. Human salivary α-amylase (HAS), porcine pancreatic α-amylase, acarbose and hydrolysable tannin from Chinese gall nut were obtained from Sigma-Aldrich Co. The Acacia mearnsii bark tannin was purchased from Labsynth, Brazil. The kinetic experiments with the HAS and pancreatic α-amylase were carried out at 37 oC in 20 mM phosphate buffer pH 6.9 containing 6.7 mM NaCl. Potato starch (Sigma-Aldrich) was used as substrate. Substrate and one of the three inhibitors, acarbose, condensed tannin or hydrolysable tannin were mixed and the reaction was initiated by adding the enzyme. The reaction was allowed to proceed for 5 min. The produced reducing sugars were assayed by the dinitrosalicylic acid method, using maltose as standard. Statistical analysis of the data was done by means of the Statistica program (Statsoft, Inc., Tulsa, OK). Fitting of the rate equations to the experimental initial rates was done by means of an iterative non-linear least-squares procedure using the Scientist software from MicroMath Scientific Software (Salt Lake City, UT). The decision as to the most adequate model (equation) was based on the model selection criterion (MSC) and on the standard deviations of the optimized parameters. Male healthy Wistar rats weighing 200 250 g were used in all in vivo experiments. Rats were divided into 9 groups (n = 4 rats per group). To group I (positive control) commercial corn starch (1 g per kg body weight) was administered intragastrically. Group II (negative control) received only tap water. Group III received intragastrically commercial corn starch plus acarbose (50 mg/kg). Groups IV, V and VI received intragastrically commercial corn starch plus A. mearnsii tannin 100, 250 and 500 mg/kg respectively. Finally, groups VII, VIII and IX received intragastrically commercial corn starch plus tannic acid extracts 100, 250 and 500 mg/kg respectively. The amounts of inhibitors given to the rats were based on literature data (Ikarashi et al., 2011). Fasting blood glucose levels were determined before the administration of starch and amylase inhibitors (0 time). Later evaluations of blood glucose levels took place at 15, 30, 45 and 60 min. Blood glucose from cut tail tips was determined using Accu-Chek® Active Glucose Meter. In the article 1, both tannins inhibited the enzyme. At a starch (substrate) concentration of 1 g/100 mL the concentrations for 50% inhibition (EC50) were 240 μg hydrolysable tannin per mL and 200 μg condensed tannin per mL. For acarbose the EC50 value was 2.2 μg/mL. The kinetics of the inhibition presented a complex pattern in that for both inhibitors more than one molecule can bind simultaneously to either the free enzyme of the substrate-complexed enzyme (parabolic mixed inhibition). The same phenomenon was found for acarbose. This is revealed a priori by the non-linear 1/v versus [I] plots and by the successful fitting of kinetic equations containing squared inhibitor concentration terms (e.g., [I]2). Both tannins were able to inhibit the intestinal starch absorption, as revealed by starch tolerance tests in rats. Inhibition by the hydrolysable tannin was concentration-dependent, with 53% inhibition at the dose of 100 mg/kg and 88% inhibition at the dose of 500 mg/kg. For the condensed tannin, inhibition was not substantially different for doses between 100 mg/kg (49%) and 500 mg/kg (57%). It can be concluded that both tannins, but especially the hydrolysable one, could be useful in controlling the post-prandial glycemic levels in diabetic patients. In the article 2, in the experiments using HAS, it was possible to calculate the IC50 values (inhibitor concentration producing 50% inhibition) for a starch concentration of 1 g/100 mL of 80 μg/mL and 230 μg/mL for the hydrolysable and condensed tannins, respectively. From the kinetic analysis it can be concluded that inhibition of the HSA by both tannins is of the mixed (or non-competitive) type. The free HSA binds the hydrolysable tannin with higher affinity considering that the Ki1 value was 22.4±2.9 μg/mL while the Ki1 value for condensed tannin was 157.1±12.6 μg/mL. Taking into account that HSA has an important role in the dental plaque formation and subsequent dental caries formation, the strong inhibitory action of the hydrolysable tannin could make it an useful agent for oral health.